An Ethnobotanical Study of Medicinal Plants Used by Kumal and Gandarva Community of Pokhara Metropolis, Kaski, Nepal - Bastakoti, Narayan Datta (Himalayan Biodiversity, 2019)
The study of indigenous knowledge about the use of medicinal plants among Kumal and Gandharva ethnic groups residing in Pokhara Metropolis, was carried out from January to April 2019. A semi-structured questionnaire survey was conducted with 77 respondents of 40 and above age group (44 Kumal and 33 Gandharva). Altogether 80 plant species of medicinal value belonging to 75 genera under 48 families including 5 species of Pteridophytes have been recorded from the study area. The family Asteraceae and Fabaceae were found with higher number of species, 7 of each. A total of 45 plants species were found used by both ethnic groups in their medical purpose; 65 species were used by Kumal, while 60 species were used by Gandharva. These plant species have been used for the treatment of a total of 39 different human ailments, grouped under 10 major diseases.